«Sextina» de Enric Casassas: Un ejemplo de vanguardismo catalan - Gregori i Gomis, Alfons (Wydawnictwo Naukowe UAM, 2003)
Being one of the best-known poets of the still-alive vanguard generation in Catalonia because of his poignant poems recitations, in his book Comenęament dels comenęaments i ocasió de les ocasions (Beginning o f Beginnigs and Occasion o f Occasions) Enric Casassas rebuilds a medieval composition, the in-baroque-times-developed sextina, which takes the form of a poem entitled “Sextina”. The author introduces a set of new elements giving the poem a metapoetics dimension. At the same time, its verses describe a subtle formal incursion into the ideological confrontation of some Catalan literary movements. It concludes with a romanticism and vanguard antibourgeois deal. In that frame, the poem is analysed from the point of view of three different approaches: A versified reconsideration of some Aristotelian concepts, desire as an unreachable Freudian lack and the performance of sexual voice playing the role of an actual poetry-producing power.